2015
DOI: 10.1074/jbc.m114.592758
|View full text |Cite
|
Sign up to set email alerts
|

The Anoctamin Family Channel Subdued Mediates Thermal Nociception in Drosophila

Abstract: Background: Subdued is a calcium-activated chloride channel of the anoctamin family in Drosophila. Results: Knockout or knockdown of subdued leads to defective nociceptive responses to heat. Conclusion: The Subdued channel mediates thermal nociception. Significance: An anoctamin channel participates in thermal nociception in insects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…These results suggest that the passive Cl − transport in Class IV neurons is outward and generates depolarizing currents but not hyperpolarizing ones. In parallel, we investigated the role of one of the Ca 2+ -activated Cl − channels, Subdued ( Jang et al, 2015 ), and showed that it can contribute to membrane excitation in the neurons ( Figure 2—figure supplement 1 ). Thus, we excluded Cl − channels as candidate sources of hyperpolarizing currents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the passive Cl − transport in Class IV neurons is outward and generates depolarizing currents but not hyperpolarizing ones. In parallel, we investigated the role of one of the Ca 2+ -activated Cl − channels, Subdued ( Jang et al, 2015 ), and showed that it can contribute to membrane excitation in the neurons ( Figure 2—figure supplement 1 ). Thus, we excluded Cl − channels as candidate sources of hyperpolarizing currents.…”
Section: Resultsmentioning
confidence: 99%
“… The gating property of subdued channels is dependent on heat, voltage and Ca 2+ , and the expression in Class IV neuron is required for larval heat avoidance behavior ( Jang et al, 2015 ). Considering the results of the Cl − ion direction ( Figure 2B–C ), the possibility of subdued channels contributing to inhibitory currents is low, although an effect of the Subdued channels on neuronal activity cannot be completely excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Larval thermal nociception assays were performed as previously described . Briefly, third instar larvae were placed on 2% agarose medium in 55 × 12‐mm plastic Petri dishes, and their abdominal segments were touched with a soldering iron with a 0.6‐mm‐wide chisel; its temperature was measured with an electronic thermometer.…”
Section: Methodsmentioning
confidence: 99%
“…Touch sensation was performed as described . Briefly, the mouth parts of third larvae were touched gently with a fine brush (n = 15, 3 times).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation